2012
DOI: 10.1093/ntr/nts153
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Plain and Branded Cigarette Packaging Among Norwegian Youth and Adults: A Focus Group Study

Abstract: The findings indicate that packaging is vital to consumer identification with and differentiation between cigarette brands and that a policy of plain packaging could be useful in reducing the impact of packaging in promotion of tobacco products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…The results indicate further that a shift from branded to plain cigarette packaging could lead to a reduction in positive perceptions of cigarettes among adolescents, also in a context where marketing of tobacco as well as extensive use of innovative pack design to attract the consumers is already highly regulated. The result that the respondents so clearly make distinctions regarding harmfulness and ease of quitting between the brand varieties based upon colours and descriptors confirms the findings from a previous qualitative research in Norway16 and points towards the conclusion that cigarette descriptors such as ‘rounded taste’ (in contrast to ‘rough taste’) and colour codes such as ‘gold’ or ‘pale blue’ are perceived in a similar way as the prohibited terms ‘light’ and ‘mild’. The use of these terms thus appears to violate the guidelines of the WHO Framework Convention on Tobacco Control treaty, which forbids information that directly or indirectly creates the false impression that a particular tobacco product is less harmful than other tobacco products.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results indicate further that a shift from branded to plain cigarette packaging could lead to a reduction in positive perceptions of cigarettes among adolescents, also in a context where marketing of tobacco as well as extensive use of innovative pack design to attract the consumers is already highly regulated. The result that the respondents so clearly make distinctions regarding harmfulness and ease of quitting between the brand varieties based upon colours and descriptors confirms the findings from a previous qualitative research in Norway16 and points towards the conclusion that cigarette descriptors such as ‘rounded taste’ (in contrast to ‘rough taste’) and colour codes such as ‘gold’ or ‘pale blue’ are perceived in a similar way as the prohibited terms ‘light’ and ‘mild’. The use of these terms thus appears to violate the guidelines of the WHO Framework Convention on Tobacco Control treaty, which forbids information that directly or indirectly creates the false impression that a particular tobacco product is less harmful than other tobacco products.…”
Section: Discussionsupporting
confidence: 85%
“…Studies from other countries evaluating the suitability of different colours have, for example, concluded that grey is perceived less negatively than brown 24. This concern is, to some extent, reduced by findings from qualitative studies indicating that grey plain cigarette packages are perceived negatively in Norway 16. The between-subjects design also carries with it some challenges, predominantly the risk of uncontrolled variation between the groups, or in this case, between the conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The public health debate addresses three main themes: (i) reduction of the symbolic value of tobacco packaging (Wakefield et al, 2012;Borland et al, 2013;Ford et al, 2013a;Moodie and MacKintosh, 2013;Scheffels and Saebø, 2013); (ii) reinforcement of consumers' health attitude towards smoking, increased recall and perceived seriousness of health messages (Hammond et al, 2009;Munafò et al, 2011;AlHamdani, 2013;Maynard et al, 2013;Moodie and MacKintosh, 2013); (iii) evidence of behavioural change (e.g., attempts to quit, quit-line calls, reduced consumption; Moodie et al, 2012Chantler, 2014;Maynard, 2014). For a systematic review of plain packaging conducted from a public health perspective, see Moodie et al (2012.…”
Section: Introductionmentioning
confidence: 99%